Technical and Regulatory Considerations for Taking Liquid Biopsy to the Clinic: Validation of the JAX PlasmaMonitorTM Assay. Issue 14 (January 2019) - Sisson, Bridgette A; Uvalic, Jasmina; Kelly, Kevin; Selvam, Pavalan; Hesse, Andrew N; Ananda, Guruprasad; Chandok, Harshpreet; Bergeron, Daniel; Holinka, Lauren; Reddi, Honey V
The standard of care in oncology has been genomic profiling of tumor tissue biopsies for the treatment and management of disease, which can prove to be quite challenging in terms of cost, invasiveness of procedure, and potential risk for the patient. As the number of available drugs in oncology continues to increase, so too does the demand for technologies and testing applications that can identify genomic alterations targetable by these new therapies. Liquid biopsies that use a blood draw from the diseased patient may offset the many disadvantages of the invasive procedure. However, as with any new technology or finding in the clinical field, the clinical utility of an analytical test such as that of the liquid biopsy has to be established. Here, we review the clinical testing space for liquid biopsy offerings and elucidate the technical and regulatory considerations to develop such an assay, using our recently validated PlasmaMonitor TM test.